Analytical Methods for the Detection and Quantification of ADCs in Biological Matrices - Héloïse Cahuzac; Laurent Devel (MDPI AG, 2020)
Understanding pharmacokinetics and biodistribution of antibody-drug conjugates (ADCs) is a one of the critical steps enabling their successful development and optimization. Their complex structure combining large and small molecule characteristics brought out multiple bioanalytical methods to decipher the behavior and fate of both components in vivo. In this respect, these methods must provide insights into different key elements including half-life and blood stability of the construct, premature release of the drug, whole-body biodistribution, and amount of the drug accumulated within the targeted pathological tissues, all of them being directly related to efficacy and safety of the ADC. In this review, we will focus on the main strategies enabling to quantify and characterize ADCs in biological matrices and discuss their associated technical challenges and current limitations.